Influence of the geological structure on a rockslide in northeastern italy - Zampieri, Dario; Adami, Silvano (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="[null,2,"In the Astico Valley (Venetian Pre Alps, north east Italy) a rockslide of approximately 10x106 m3 occurred in conjunction with the Verona earthquake (03.01.1117, I0 IX MCS, M 7.0). The rockslide seems to have been favoured by the downhill dip of the carbonate beds and the deposit dammed the narrow valley originating a lake, later emptied by the river incision of the landslide deposit. Upwards of the crown more than 10x106m3 of rocks are still hanging on the valley. Here we present the results of a preliminary geological analysis of the slope, showing that the failure surface corresponds to a thrust surface with a stair case trajectory only partially coinciding with the beds, which has been reactivated by the rockslide. Moreover, the kinematic analysis shows that the scarp of the landslide could be involved in a quite huge new landslide. Along the Astico valley a motorway has been designed, with a viaduct and service areas just at the foot of this potential landslide. The field investigations suggest this potential landslide could have a high impact on such infrastructures and that a careful stability analysis is needed for an appropriate risk assessment."]" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">In the Astico Valley (Venetian Pre Alps, north east Italy) a rockslide of approximately 10x106 m3 occurred in conjunction with the Verona earthquake (03.01.1117, I0 IX MCS, M 7.0). The rockslide seems to have been favoured by the downhill dip of the carbonate beds and the deposit dammed the narrow valley originating a lake, later emptied by the river incision of the landslide deposit. Upwards of the crown more than 10x106m3 of rocks are still hanging on the valley. Here we present the results of a preliminary geological analysis of the slope, showing that the failure surface corresponds to a thrust surface with a stair case trajectory only partially coinciding with the beds, which has been reactivated by the rockslide. Moreover, the kinematic analysis shows that the scarp of the landslide could be involved in a quite huge new landslide. Along the Astico valley a motorway has been designed, with a viaduct and service areas just at the foot of this potential landslide. The field investigations suggest this potential landslide could have a high impact on such infrastructures and that a careful stability analysis is needed for an appropriate risk assessment.